Pengaruh Konseling Terhadap Pengetahuan Dan Kepatuhan Pada Pasien Asma Di Poliklinik Paru RSUD dr. Rasidin Padang - Edri Rovi; Hansen Nasif; Yelly Oktavia Sari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Asthma is a chronic respiratory disease characterized by airway inflammation and narrowing, leading to symptoms such as coughing, shortness of breath, and wheezing. The prevalence of asthma remains high both globally and nationally, resulting in significant health and economic burdens. Pharmacist counseling has been shown to play an important role in improving patients’ knowledge and medication adherence, thereby supporting disease control and preventing recurrence. This study employed a pre-experimental design using a one-group pretest–posttest approach. The research sample consisted of 68 outpatient asthma patients from the pulmonary polyclinic selected using purposive sampling technique. Patients’ knowledge was assessed using the Asthma General Knowledge Questionnaire (AGKQ), while medication adherence was measured using the Medication Adherence Report Scale (MARS-10). Data were analyzed using the Wilcoxon test and the Chi-Square or Fisher’s Exact test, with a significance level set at p < 0.05. The results indicated that pharmacist counseling significantly improved both knowledge and medication adherence among asthma patients (p = 0.000). However, no statistically significant relationship was found between knowledge and adherence at the pretest stage (p = 0.119) or the posttest stage (p = 1.000), which may be attributed to data homogeneity following counseling. In conclusion, pharmacist counseling is effective in enhancing knowledge and medication adherence in asthma patients. Therefore, counseling should be routinely implemented as part of clinical pharmacy services to support optimal asthma control.